Carbon Nanotube Field-Effect Transistors for High-Performance Digital Circuits-Transient Analysis, Parasitics, and Scalability - Keshavarzi, A.; Raychowdhury, A.; Kurtin, J.; Roy, K.; De, V. (IEEE transactions on electron devices, 2006)
Silicon-based CMOS is the dominant technology choice for high-performance digital circuits. While silicon technology continues to scale, researchers are investigating other novel materials, structures, and devices to introduce into future technology generations, if necessary, to extend Moore's law. Carbon nanotubes (CNTs) have been explored as a possibility due to their excellent carrier mobility. The authors studied and compared different carbon-nanotube-based field-effect transistors (CNFETs) including Schottky-barrier (SB) CNFETs, MOS CNFETs, and state-of-the-art Si MOSFETs systematically from a circuit/system design perspective. Parasitics play a major role in the performance of CNT-based circuits. The data in this paper show that CNFET design's performance is limited by the gate overlap capacitance and the quality of nanocontacts to these promising transistors. Transient analysis of high-performing single-tube SB CNFET transistors and circuits revealed that 1-1.5 nm is the optimum CNT diameter resulting in best power-performance tradeoff for high-speed digital applications. The authors determined optimal spacing and layout of CNT arrays, an architecture that is most likely required for driving capacitive loads and interconnects in digital applications. CNTs have an intrinsic capability to improve performance, but many serious technological and experimental challenges remain that require more research to harvest their potential